2016
DOI: 10.1105/tpc.16.00045
|View full text |Cite
|
Sign up to set email alerts
|

An Ancient Bacterial Signaling Pathway Regulates Chloroplast Function to Influence Growth and Development in Arabidopsis

Abstract: The chloroplast originated from the endosymbiosis of an ancient photosynthetic bacterium by a eukaryotic cell. Remarkably, the chloroplast has retained elements of a bacterial stress response pathway that is mediated by the signaling nucleotides guanosine penta-and tetraphosphate (ppGpp). However, an understanding of the mechanism and outcomes of ppGpp signaling in the photosynthetic eukaryotes has remained elusive. Using the model plant Arabidopsis thaliana, we show that ppGpp is a potent regulator of chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
247
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(274 citation statements)
references
References 69 publications
(115 reference statements)
11
247
2
Order By: Relevance
“…In Arabidopsis thaliana, all of these proteins localize to the chloroplast (19,56), and ppGpp levels rise in plants in response to darkness and other stresses, including wounding (57). Two recent studies have also shown that ppGpp levels affect photosynthetic capacity and chloroplast development in Arabidopsis (19,58). Thus, it is likely that aspects of the stringent response pathway are conserved between cyanobacteria and chloroplasts.…”
Section: Conservation and Adaptation Of Stringent Response Mechanisms Inmentioning
confidence: 99%
“…In Arabidopsis thaliana, all of these proteins localize to the chloroplast (19,56), and ppGpp levels rise in plants in response to darkness and other stresses, including wounding (57). Two recent studies have also shown that ppGpp levels affect photosynthetic capacity and chloroplast development in Arabidopsis (19,58). Thus, it is likely that aspects of the stringent response pathway are conserved between cyanobacteria and chloroplasts.…”
Section: Conservation and Adaptation Of Stringent Response Mechanisms Inmentioning
confidence: 99%
“…Surprisingly, despite decreased transcript levels, AccD protein level increases in line accumulating alarmones (Maekawa et al 2015; Sugliani et al 2016). …”
Section: Role Of Rsh Proteins and Alarmones In Chloroplastsmentioning
confidence: 99%
“…Thus, despite the very high level of homology between bacteria and plants in the RSH domain structure and function as well as molecular targets of alarmones, (p)ppGpp-mediated responses in plants become different, according to Sugliani et al (2016) likely due to the evolutionary gene transfer of vast amount of endosymbiont/plastid DNA into the host genome. Since chloroplasts do not proliferate as frequently as bacteria, it is also understandable that their DNA replication would be rather differently regulated.…”
Section: Role Of Rsh Proteins and Alarmones In Chloroplastsmentioning
confidence: 99%
See 2 more Smart Citations